Assessing alternative strategy options in the control of tick-borne disease: A case study of east coast fever control in Uasin Gishu District, Kenya - Onchoke, D.G. (University of Nairobi, 1993)
Lack of effective tick and tick-borne disease (TBD) control is among the factors limiting dairy production in Uasin Gishu District in Kenya. Besides constraining productivity through morbidity, TBDs are among the most important causes of cattle deaths, most serious being East Coast fever (ECF). In the district, ECF is currently controlled largely by controlling ticks using chemicals (acaricides) and by treating sick animals. A new technology which involves immunizing cattle against the disease has been developed and found to be feasible under research conditions. This new method of controlling ECF is intended to be introduced in Uasin Gishu District by the Kenya Government. This study was initiated with the main objective of examining the issues associated with the alternative strategy options for the control of ticks and TBDs in Uasin . Gishu District. The study examined the current control methods and compared them to alternative strategy based on immunization. Various options of the delivery systems for the control strategies were also examined. Data were gathered from a sample of 120 farmers in two divisions (Ainabkoi and Moiben) and from extension personnel in the district. Other sources of data included published and unpublished research papers, government reports and opinions from experts and researchers. The data were computerized and analyzed using relevant statistical procedures and a spreadsheet analytical model. Data from the farm survey and extension staff were used to generate tables for descriptive statistics. Where appropriate, comparison methods (Chi-square and Analysis of Variance) were used on individual variables to find out whether differences existed among them within and between divisions. The farm survey achieved 100% response rate. There was a high diversity in sizes of sampled farms. They ranged from 0.5 acres to a maximum of 9000 acres. Likewise the number of cattle per household varied with farm scales ranging from 2 to 875 heads of cattle. The survey results showed eighty two percent of the farmers rated ticks and tick related problems highest among farm problems. Ninety nine percent of the farmers indicated that they practised tick control. However, the study noted that the frequency of acaricidal application was often irregular with some farmers. High costs associated with acaricidal use was rated as the main shortcoming of this method by 67 % of the farmers. Seventy five percent of the respondents felt that veterinary services were inadequate and rated the performance of the veterinary staff as being poor. It was noted that Uasin Gishu District although having enough extension staff, had no adequate operational means to facilitate their performance and enhance their effectiveness. Lack of transport, drugs, offices and equipment was evident in the two study divisions. The spreadsheet model assessed product (total beef, milk, manure and animal traction) losses from ECF mortality and morbidity, and control and treatment expenditures due to the disease (under the current control strategy of acaricide application and under alternative control scenarios using immunization). These losses were calculated by applying the disease incidence, case-fatality rates for the different classes of cattle. The total cost attributable to ECF in Uasin Gishu District in 1992 was estimated to Ksh 1113 million. Immunization showed a high economic return with a benefit : cost in the range of 4-5 for Grade cattle and 2.6-2.8 for Zebu cattle. It was estimated that a total of 221,695 heads of cattle would be targeted for immunization in the first year and would require a budget of Ksh 112 million. The results demonstrated that the current delivery of TBD control does not meet demands of veterinary services and farmers in Uasin Gishu District. These results also show that immunization-based ECF control strategy is more cost-effective than the acaricide- based strategy. It was concluded that the government veterinary service will not be effective in the delivery of the immunization method on a sustainable basis and should therefore create an enabling climate for a private practitioner who can be more efficient in delivering this service to farmers in Uasin Gishu District. Description: